Calabaza—Cucurbita moschata Duch. ex Lam. - James M. Stephens (EDIS)
This document provides an overview of calabaza (Cucurbita moschata), commonly known as Cuban pumpkin or squash, detailing its cultivation, description, and uses. Calabaza is a vining plant with mottled green or yellow fruits, grown primarily in South Florida. It thrives in hot weather and requires about three months from seeding to harvest. The document highlights cultural practices, including spacing and composting, and mentions common issues like downy mildew. Calabaza is popular among Latin communities in Florida, who use it in various traditional recipes. Original publication date April 1994.